Biological control of vascular wilt by Trichoderma spp. for peanut crops - Romero-Arenas, Omar; Parraguirre-Lezama, Conrado; Huerta-Lara, Manuel; Martínez-Salgado, Saira Jazmín; Andrade-Hoyos, Petra; Rivera, Antonio (Revista Mexicana de Ciencias Agrícolas, 2025)
In Mexico, peanut crops are a productive activity in rural areas; nevertheless, they are threatened by fungal diseases, such as vascular wilt, caused by Fusarium incarnatum, recently reported in the country. The study assessed the antagonistic capacity of five Trichoderma species against the ‘MA-PET-03’ strain of F. incarnatum in peanut crops in Buenavista de Benito Juárez, Chietla, Puebla. It was highlighted that T. koningiopsis showed the highest growth rate and the highest percentage of radial growth inhibition (PRGI) of F. incarnatum in in vitro tests. Under field conditions, treatments with Trichoderma spp. had more peanut pods per plant and lower incidence of the disease, improving crop yield. These results confirm the effectiveness of Trichoderma spp. for managing vascular wilt in the region.